Mekanisme Pertahanan Diri Sigmund Freud Pada Tokoh Margio Dalam Novel Lelaki Harimau Karya Eka Kurniawan - Adi Prastya, Tommy; Muharram, Farid Ikmal; Kurniawan, Eva Dwi (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2023)
This research aims to find out how the self-defense mechanism of Margio's character in the novel Lelaki Harimau by Eka Kurniawan. The problem raised is how the self-defense mechanism is carried out by the character Margio in the novel Lelaki Harimau by Eka Kurniawan when facing a problem. This research uses a qualitative method and is presented descriptively. The data in this study are in the form of words or sentences. The theory used comes from one of the most famous psychoanalysts, Sigmund Freud. The findings obtained from this study are the form of self-defense mechanisms carried out by the character Margio in the novel Lelaki Harimau by Eka Kurniawan in the form of Repression, Rationalization, Diversion, Projection, Denial, and Regression. This research only focuses on one character, namely Margio. Future research can discuss other characters and study them more broadly.